Fishing Gears Assessment Based on Code of Conduct for Responsible Fisheries (CCRF) at Probolinggo - Ade Hanafi; Harsuko Riniwati; Aminudin Afandhi (Graduate Program, 2019)
The exploitation level of capture fisheries along the north of Java has reached the recommended MSY. The increasing number and size of fishing gear and ships, as well as the expansion of operations to new fishing areas have resulted in over-exploitation. Research purposes to analyze fishing gear that applies eco-friendly criteria in accordance with the code of conduct responsible fisheries in the Probolinggo City . The research method uses descriptive method, with quota sampling technique. Analysis based on environmentally friendly dental weighing criteria issued by the marine and fisheries department in 2006. Where each of criterion has 4 sub-criteria assessed by scoring from weighting, while the eco-friendly gear category is divided into 4 categories with a range of values as follows: 1-9 i.e. very unfriendly gear, 10-18 i.e. unfriendly gear, 19-27 i.e. Eco-friendly gear, 28-36 i.e. gear is very eco-friendly. The study results fishing gears which are categorized as very eco-friendly, purse seine (31,77), hand line (33,61), pot fish (34,70), lift net (31,10), and gillnet (32,53), just only cantrang (23.28) is included in the eco-friendly. Fishing gear that is very eco-friendly is recommended in the City of Probolinggo, pot fish, hand line, gill net, purse seine, and lift net.